Дослідження деформаційного впливу в процесі додаткового фрикційно-деформаційного зміцнення сталей - Волков, Олег Олексійович; Субботіна, Валерія Валеріївна; Погрібний, Микола Андрійович; Терлецький, Олександр Семенович; Юшко, Анастасія Вадимівна; Федоренко, Ганна Анатоліївна (Національний технічний університет "Харківський політехнічний інститут", 2025)
Досліджено, як впливає деформаційна складова на структурний стан і властивості сталей у процесі додаткового фрикційно-деформаційного зміцнення (ДФДЗ). Поєднання теплового та механічного впливів спричиняє суттєві структурні перетворення в приповерхневих шарах матеріалу. За допомогою дюрометрічних досліджень та з використанням результатів металографічного аналізу, що отримані раніше, визначено особливості зв’язку між еволюцією мікроструктури та зміною властивостей в полі впливу деформації при ДФДЗ поверхні. Наведено результати досліджень зразків і проаналізовано вплив деформаційної складової на розподіл мікротвердості в перерізі зразків сталей з різним вмістом вуглецю.

The influence of the deformation component on the structural state and properties of steels during the process of additional friction-deformation strengthening (AFDS) has been investigated. It is known that during FDS, the simultaneous action of thermal flows and mechanical loads creates a complex stress–strain state in the near-surface layers of the material. The combination of thermal and mechanical energy causes intensive structural transformations manifested in the formation of fine-grained or even nanostructured regions, the development of deformation texture, and changes in phase composition. Special attention in the study is given to the role of elastic and plastic deformation in the strengthening mechanisms. Elastic deformation, although it does not leave permanent structural changes, determines the distribution of instantaneous stresses in the contact zone and influences the initiation of plastic shifts. Plastic deformation, which is dominant during AFDS, leads to the accumulation of dislocations, the formation of subgrains, and an increase in the defectiveness of the crystal lattice. These processes ensure a significant increase in microhardness and the development of a strengthened layer with improved mechanical characteristics. Using durometric examinations, as well as previously obtained metallographic analysis data, the relationship between microstructural evolution and changes in material properties under the action of deformation has been established. The results of microhardness measurements are presented, and the influence of the deformation component on its distribution across the cross-section of steel specimens with different carbon contents is analyzed. It is shown that an increase in the proportion of plastic deformation promotes the formation of a deeper and more uniform strengthened layer, while the ratio of elastic to plastic deformation determines the hardness gradient and structural heterogeneity within the zone affected by AFDS.
Investigation of the deformation effect in the process of additional friction-deformation strengthening of steels
Keywords: додаткове фрикційно-деформаційне зміцнення; поверхня; нагрівання; пружна деформація; пластична деформація; наклеп; структура; "білий шар"; білий шар; мікротвердість; additional friction-deformation strengthening; surface; heating; elastic and plastic deformation; work hardening; structure; "white layer"; microhardness